Evaluasi Sistem Budidaya Tanaman Asystasia gangetica T. Anderson yang Ditanam dengan Jarak Berbeda di Bawah Naungan Kelapa Sawit - H Herilimiansyah; N R Kumalasari; L Abdullah (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2019)
The objective of this experiment was to evaluate the cultivation, production and quality systems of Asystasia gangetica T. Anderson as forage in palm oil plantations. This research was arranged in a factorial randomized block design with 2 factors, i.e. palm plantation ages (6 and 8 years old) and different plant spacing (10x10 cm, 25x25 cm, and 40x40 cm). Variables observed were plant height, number of leaves, number of primary and secondary branches, leaf length and width, biomass production, and nutrient contents. Spacing was significantly affected (p<0.05) on increasing height plant, number of primary and secondary branches, number of leaves, leaf width and length, and biomass production. The spacing also has a significant effect (p<0.05) on nutrient content such as dry matter and crude fiber. The heighest plants average at plant spacing of 10x10 cm was 66.19 cm, the best number of primary and secondary branches at spacing of 25x25 cm were 2 and 10 branches, the average number of the best number of leaves at spacing of 25x25 cm was 80 leaflets, leaveslength and width at spacing of 10x10 cm were 12.49 and 4.29 cm, while the best biomass production at spacing of 10x10 cm was 2766 g. The research concluded that in order to obtain high crop production, the best plant spacing was 10x10 cm under 6 years old of palm plantation, whereas the best nutrient quality was on 25x25 cm spacing. Keywords: Asystasia, Forage, nutrient content, plant spacing